(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study was undertaken to assess the phytochemical and pesticidal activities of Clerodendrum phlomidis stem, leaf, root and flower extracts. Bioactive compounds were extracted using acetone, benzene, ethanol n- butyl alcohol and isopropyl alcohol for phytochemicals investigation. Most of the extract revealed the presence of alkaloid, flavonoid, phenol, tannin and saponin, carbohydrate, glycosides, proteins, terpenoids. Plants may form an alternative sources of mosquito control agents. The present study also assessed the larvicidal activity of stem, root, leaves and flower of Clerodendrum phlomidis L.F. plant parts collected, dried, powdered then extracted using acetone, benzene, ethanol n- butyl alcohol and isopropyl alcohol. Larvicidal activity conducted by serial dilution methods in different concentrations such as 100, 200, 300,400 and 500 ppm. The larval mortality was calculated after 12 h and 24h of the exposure period. LC50 and LC90 values were calculated by probit analysis. All plant extracts showed significant larvicidal activity against A. aegypti mosquito larvae. Among the extract tested, the n-butyl alcohol extract recorded the highest activity in all the extracts. In comparing plant parts, root shows more activity than other parts. Root of n- butyl alcohol extract attaining 87% mortality against Aedes aegypti after 24h of exposure period. Present study reveals that plant extracts as biocidal agent against mosquito larvae. Our data suggest that the stem, root, leaves, flowers of n-butyl alcohol extract of Clerodendrum phlomidis have the potential to be used as an eco-friendly approach for the control of the Aedes aegypti.